School and drugs: Closing the gap - Evidence from a randomized trial in the US - Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2012)
We present evidence on how The Quantum Opportunity Program (QOP hereafter) worked in the US. While the program was regarded as successful in the short-term, in the long-run its educational results were modest and its effects on risky behaviors detrimental. Exploiting control group's self-reported drug use while in school, we evaluate whether the program worked best among those with high-predicted risk of problem behavior. We find QOP to be extremely successful among high-risk youths as it managed to curb their risky behaviors during high-school and, by doing so, it persistently improved high-school graduation by 20 percent and college enrollment by 28 percent. In contrast, QOP was unsuccessful among youths in the bottom-half of the risk distribution as it increased their engagement in risky behaviors while in high-school. Negative peer effects are possibly an explanation behind these results. Finally, negative peer effects also seem to explain the longer-run detrimental effects of QOP on risky behaviors.
Keywords: C93; I21; I22; I28; J24; 330; mentoring programs; peer effects; risky behaviors; educational programs; randomized trials; Jugendpolitik; Gesundheitsvorsorge; Wirkungsanalyse; Drogenkonsum; Soziale Gruppe; USA